G.I. Joe [videorecording (DVD)] : retaliation - Chu, Jon M. (Jon Murray), 1979-; Pryce, Jonathan; Yi, Pyŏng-hŏn, 1970-; Johnson, Dwayne, 1972-; Willis, Bruce, 1955-; Tatum, Channing (Paramount Home Entertainment, 2013)
An elite military unit, comprised of special operatives known as G.I. Joe, has been set up to take the fall for a terrible crime they didn't commit. Now, Roadblock, Duke, and the others must once again face their mortal enemy, COBRA, as well as dangerous new threats operating within the government. When all else fails, one option remains: Retaliation.